The Influence of Sustainable Omnichannel Operations on MSMEs’ Sustainable Performance: The Mediating Role of Big Data Analytics Capability and Dynamic Capabilities - Muhammad Yofie Pratama; Siti Nursyamsiah (Danadyaksa: Post Modern Economy Journal, 2026)
This study examines the effect of Sustainable Omnichannel Operations (SOO) on Sustainable Performance (SP) among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through the mediating roles of Big Data Analytics Capability (BDAC) and Dynamic Capabilities (DC). A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with data collected from 331 MSME owners and managers implementing integrated online and offline sales channels. The findings reveal that SOO positively and significantly affects BDAC, DC, and Sustainable Performance. In addition, BDAC positively influences both DC and Sustainable Performance and successfully mediates the relationships between SOO–DC and SOO–SP. However, Dynamic Capabilities were found to have no significant effect on Sustainable Performance and failed to mediate the relationships involving Sustainable Performance. These findings indicate that MSMEs’ sustainable performance is more strongly influenced by data-driven analytical capability than by organizational adaptability alone. This study contributes to the sustainable digital transformation literature by providing empirical evidence on the integrated relationships among SOO, BDAC, DC, and Sustainable Performance within the MSME context.